2017
DOI: 10.1016/s2542-5196(17)30136-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of air particulate pollution with bone loss over time and bone fracture risk: analysis of data from two independent studies

Abstract: Background Air particulate matter (PM) is a ubiquitous environmental exposure associated with oxidation, inflammation, and age-related chronic disease. Whether PM is associated with loss of bone mineral density (BMD) and risk of bone fractures is undetermined. Methods We conducted two complementary studies of: (i) long-term PM <2.5 μm (PM2.5) levels and osteoporosis-related fracture hospital admissions among 9.2 million Medicare enrollees of the Northeast/Mid-Atlantic United States between 2003–2010; (ii) lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 61 publications
8
88
1
Order By: Relevance
“…Air pollution caused oxidative damage and inflammation and resulted in the cytotoxic responses in the body [72][73][74][75][76] . Air pollution was found to cause inflammation, leading to accelerated bone loss and increased risk of bone fracture and osteoporosis 77 . Exposure to air pollution is associated with oxidative damage to DNA and lipids in humans 78 .…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution caused oxidative damage and inflammation and resulted in the cytotoxic responses in the body [72][73][74][75][76] . Air pollution was found to cause inflammation, leading to accelerated bone loss and increased risk of bone fracture and osteoporosis 77 . Exposure to air pollution is associated with oxidative damage to DNA and lipids in humans 78 .…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal design might have increased our statistical power and precision of the estimates. 10 Second, we relied on selfreported primary fuel use measured by questionnaires, which likely resulted in exposure misclassification that may have biased our estimates toward the null. We did not have data on the lifetime history of household biomass fuel use.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Evidence evaluating the association between PM and skeletal health is limited. 9 Some studies 10,11 have observed associations between PM and lower bone mineral density (BMD), increased BMD loss, or increased risk of osteoporotic fracture. However, other studies have study follows the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guideline for cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%
“…Annual average of concentrations of (MP 2,5 ) in μg/m 3 2.5 and excessive loss of longitudinal bone. They also found that the population of areas with a higher concentration of PM 2.5 have a higher risk of suffering an osteoporotic fracture 6 .…”
Section: Table 1 Annual Average Of Concentrations Of Fine Particulatmentioning
confidence: 96%